Analisis Kerentanan Bahaya Gempa Bumi Tektonik Merusak Berdasarkan Fungsi Atenuasi Zhao Di Nusa Tenggara Timur - Irjan Irjan; ahmad luthfin; Septiana Nur Hidayati (Department of Physics, Sebelas Maret University, 2022)
The East Nusa Tenggara (NTT) region which is located between 2 earthquakes, namely the tectonic plate subduction zone in the south and the Back Arc Thrust zone in the north, is very interesting to study considering the very active tectonic earthquakes that are significantly destructive in this region which have earthquake characteristics shallow and large magnitude. A study has been carried out that aims to determine the vulnerability of the tectonic earthquake to significant damage when seismic waves pass through these islands. The vulnerability information generated can be useful as a reference for disaster mitigation and factors that need to be considered before carrying out development in the NTT region. The input data studied are shallow earthquake data from 1997-2018 at a depth of 60 km and a magnitude M≥5 SR at coordinates 8o 30’-13o 10’ South Latitude and 118o 30’-125o 30’ East Longitude. The number of earthquake events is 198 data. The attenuation function used refers to the attenuation function Zhao, et. al 2006. The results of the study show that. the vulnerability of the tectonic earthquake to significant damage in the East Nusa Tenggara region clustered on the MMI V-VIII intensity scale. Most of these islands are clustered on the MMI VII-VIII intensity scale and only a small part is clustered on the V-VI MMI intensity scale. The NTT region which has an intensity scale of VII-VIII MMI has a high vulnerability to destructive earthquakes, so it is necessary to disseminate disaster mitigation from an early age to the public about the threat of earthquakes and it is recommended that this information be used as a reference in developing the area.